Comparison of mono-exponential, bi-exponential, and stretched exponential diffusion-weighted MR imaging models in differentiating hepatic hemangiomas from liver metastases. Issue 141 (August 2021) - Fujimoto, Keita; Noda, Yoshifumi; Kawai, Nobuyuki; Kajita, Kimihiro; Akamine, Yuta; Kawada, Hiroshi; Hyodo, Fuminori; Matsuo, Masayuki
Highlights: Stretched exponential diffusion-weighted imaging (DWI) was feasible in clinical MR imaging evaluation of the liver lesions. The distributed diffusion coefficient (DDC) value was useful for differentiating hepatic hemangiomas and liver metastases. ADC and DDC values had the highest diagnostic performance for differentiating hepatic hemangiomas and liver metastases. Abstract: Purpose: This study aims to compare the diagnostic values of mono-exponential, bi-exponential, and stretched exponential diffusion-weighted imaging (DWI) in differentiating hepatic hemangiomas and liver metastases. Method: This prospective study was approved by our institutional review board, and written informed consent was obtained from all patients. In this study, 244 patients with known or suspected liver disease underwent magnetic resonance imaging. Among them, 37 patients who had focal hepatic lesions with a maximum diameter of ≥10 mm were evaluated. Using home-built software, two radiologists measured the DWI parameters of hepatic lesions for the three models: the apparent diffusion coefficient (ADC) from a mono-exponential model; the true diffusion coefficient ( D ), pseudo-diffusion coefficient ( D *), and perfusion fraction ( f ) from a bi-exponential model; and the distributed diffusion coefficient (DDC) and water molecular diffusion heterogeneity index (α) from a stretched exponential model. The parameters were compared between hepatic hemangiomas and liver metastases. Results: In total, 64 focal hepatic lesions were evaluated, of which 22 were identified to be hepatic hemangiomas and 42 were liver metastases. ADC, D, f, and DDC values were significantly lower in liver metastases than in hepatic hemangiomas ( P  <  0.0001,  <  0.0001, 0.015, and <  0.0001, respectively); whereas, the α value was significantly higher in liver metastases than in hepatic hemangiomas ( P  =  0.028). The areas under the ROC curve (AUCs) for differentiating hepatic hemangiomas and liver metastases in ADC, D, D *, f, DDC, and α were 0.940, 0.908, 0.608, 0.686, 0.952, and 0.667, respectively. The AUC values of ADC and DDC were significantly greater than those of D* ( P  <  0.0001), f ( P  =  0.0001), and α values ( P  =  0.0001). Conclusion: ADC and DDC values from the mono-exponential and stretched exponential models could be considered as quantitative imaging biomarkers for differentiating hepatic hemangiomas and liver metastases.